2007
DOI: 10.1787/eco_studies-v2006-art8-en
|View full text |Cite
|
Sign up to set email alerts
|

Taxation and business environment as drivers of foreign direct investment in OECD countries

Abstract: How important are differences in corporate taxation for the investment decisions of multinational enterprises (MNEs)? Over the past decade, interest in this issue has been growing in parallel with the increasing mobility of capital and internationalisation of businesses. Standard models of the MNEs predict that corporate taxation can influence foreign direct investment (FDI) by creating a wedge between the pre- and post-tax returns on investment. The relevant tax wedge, however, depends on whether MNEs’ invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…In this sense, our results are in line with earlier work by e.g. Hajkova et al (2006). Significant positive effects on a country's access to global technology also follow from an increase in openness, i.e.…”
Section: Indirect Effects Of Fiscal Policysupporting
confidence: 93%
“…In this sense, our results are in line with earlier work by e.g. Hajkova et al (2006). Significant positive effects on a country's access to global technology also follow from an increase in openness, i.e.…”
Section: Indirect Effects Of Fiscal Policysupporting
confidence: 93%
“…affecting firms' location choice. For instance, their influence appears relatively small in comparison with labour taxes (Hajkova et al, 2006).…”
mentioning
confidence: 98%
“…Indeed, a recent OECD study found that tax planning reduces the effect of corporate taxation on investment of taxplanning MNEs (OECD, 2015c). There is also a vast literature, including past OECD work, suggesting an adverse effect of the host country corporate tax rate on foreign investment (Hajkova et al, 2006;Feld and Heckemeyer, 2011). But corporate taxes are only one among many factors (e.g.…”
mentioning
confidence: 99%
“…Fiscal Policy and Growth in Developing Asia | 11 Corporate income taxes are expected to be harmful to growth because they discourage investment in capital and productivity improvements in addition to reducing foreign direct investment (Arnold et al 2011, Myles 2009, and Hajkova et al 2006). Owing to their progressive nature, personal income taxes can discourage growth more per unit of tax revenue than consumption taxes, which are generally flat.…”
Section: Quantifying the Impact On Growth Of Fiscal Policy Changesmentioning
confidence: 99%